REAÇÃO DE CULTIVARES DE SOJA AO CANCRO DA HASTE (Diaporthe phaseolorum f. sp meridionalis) - Lopes, Maria Elizabete Barretto M.; Barros, Benedito de Camargo; Papa, Marli de Fátima Stradioto; Menten, José Otávio Machado (REVISTA DE AGRICULTURA, 2015)
REAÇÃO DE CULTIVARES DE SOJA AO CANCRO DA HASTE (Diaporthe phaseolorum f. sp meridionalis)